Standardization of Ayurvedic Drug- Nyctanthes arbor-tristis, Hippophae salicifolia, Ocimum tenuiflorum and Reinwardtia indica and Combined Herb-Herb - Kumari, Rinki; Dubey, G.P. (Nepal Journal of Biotechnology, 2020)
The herbal medicines have reached extensive acceptability as therapeutic agents for various clinical diseases due to global demand. Therefore, standardization is the essential and initial step to drug development. It is for the establishment of consistent biological activity, a consistent chemical profile and biomarker identification. It improves the safety and efficacy of herbal medicine to provide the best herbal medicine to society and increase popularity rather than non-standardized extracts. In addition, it is essential to practice or maintain a quality assurance program for the production and manufacturing of herbal medicine that includes the basis of organoleptic characters and photomicrographs, physicochemical, proximate analysis phytochemical evaluation and quality control analysis and order to assess the quality of drugs, based on the concentration of their active principles. WHO has provided specific guidelines for the assessment of the safety, efficacy and quality of herbal drugs as a prerequisite for global harmonization and of utmost importance. In the present study, the herbal extracts were cleaned, dried in the shade and powdered by passing through the sieve as per the method described in the standard protocol. An overview covering various techniques employed in the extraction and characterization of Nyctanthes arbortristis, Hippophae salicifolia, Ocimum tenuiflorum and Reinwardtia indica, standardization is reported in this study. The obtained data would be very significant for future clinical aspects, as the bioactive molecules present in the extracts may exhibit synergistic effect with other bioactive compound and show a better therapeutic value. Thus, this study provides standardized and therapeutically potential data of active polyherbal formulations for the different ailments.